69.5k views
5 votes
What solution shows a correct way of simplifying 6-4(2-5x) A.) - 4(2-5x)=6-4(-3x)=6+12x B.)6-4(2-5x)=6-8+20x= -2+20x C.) 6 -4(2-5x)=2(2-5x)=4-10x D.) 6-4(2-5x)=6-8-20x= -2 -20x

1 Answer

3 votes

Answer:

B.)6-4(2-5x)=6-8+20x= -2+20x

Explanation:

Given expression is
6-4(2-5x).

We have to find out the correct way of simplifying from the 4 options.

Simplifying should be done using 'PEDMAS' rule and also sign should be correct.

A.)6 - 4(2-5x)=6-4(-3x)=6+12x

Here the '2' subtracted from '
5x' in the parenthesis.

But '2' is a constant term whereas '5x' is variable, so we can't do subtraction.

So this is not the correct way of simplifying.

B.)6-4(2-5x)=6-8+20x= -2+20x

Here 'PEDMAS' rule is followed.

According to this '4' is multiplied with firstly '2' and then '-5x', giving the result '-8' and 20x.

And then combing the like terms and get the answer
-2+20x.

So this is the correct way of simplifying.

C.) 6 -4(2-5x)=2(2-5x)=4-10x

Here PEDMAS rule is not followed.

'-4' is subtracted from '6' and get '2' and then multiplied with
(2-5x).

So this is not the correct way of simplifying.

D.) 6-4(2-5x)=6-8-20x= -2 -20x

Here 'PEDMAS' rule is followed.

But the negative sing of 5x is not changed into positive sign with thw answer 20x.

So this is also not the correct way of simplifying.

User Jan Ajan
by
5.0k points